ANALISIS PERAN KOMUNIKASI BISNIS DALAM MENINGKATKAN EFEKTIVITAS KERJA AUDITOR (STUDI KASUS DI KAP XYZ) - Ananda Rachmania Salsabilla; Febry Fabian Susanto (CV. Denasya Smart Publisher, 2025)
In the face of intensifying competition in the era of globalization, companies must adapt and innovate to survive. Effective communication is a key factor determining the success of a business entity. In a professional business context, this effective communication is known as business communication. Based on the identified research gap, this study aims to deeply analyze the implementation of business communication in enhancing auditor work effectiveness, with a case study at Public Accounting Firm (KAP) XYZ Surabaya. This research employed a descriptive qualitative method, utilizing data collected through in-depth interviews and observation at KAP XYZ. The results indicate that effective business communication is a strategic tool for improving auditor effectiveness and professionalism. Verbal communication, encompassing both spoken and written forms, functions to ensure information accuracy and facilitate smooth internal and external coordination, as well as adaptation to digital media usage. Meanwhile, nonverbal communication (facial expressions, vocal tone, body language, and chronemics) serves to maintain the auditor's objectivity, credibility, and to build client trust. The effective combination of these two forms of communication is concretely proven to enhance auditor work efficiency by minimizing crucial miscommunication, accelerating the acquisition of audit evidence from clients, and increasing trust, thereby facilitating the timely completion of all audit task stages. This finding is expected to serve as a reference for auditors, prospective auditors, and public accounting firm leaders in developing professional communication strategies that can improve the professionalism of auditor-client relationships and overall auditor work effectiveness.